The Arisan of Qurban in Islamic Economic Perspective - Syarial Dedi (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: This research aims to answer the practice of qurban social gathering that has recently developed in society. There are two interesting things that need to be discussed; the first, in the arisan to conduct the lottery, Islam views the lottery as identical with gambling and the law is strictly forbidden. The second, social gathering is essentially a debt, while qurban worship is obligatory on people who can afford it. Obviously the debtor can't afford it. The conclusions, it was concluded that social gathering is generally classified as a mu'amalat activity that contains elements of mutual assistance. This activity has never been mentioned in the Qur'an or hadith directly, the law refers to the law of origin of mu'amalah, which is permissible. Design/Method/Approach: This research is a library research with a qualitative approach, and uses content analysis techniques with the ushul al-fiqh framework.Findings:He turns into haram, if it contains elements of usury, fraud and causes losses to other parties. The essence of arisan is debt, while qurban worship is borne by capable servants as the characteristics of Islamic law are not burdensome. The leaving worship beyond one's ability is not a sin.Originality/Values: